2019
DOI: 10.7783/kjmcs.2019.27.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of a 4-Year-Old Ginseng Based on Steaming Temperatures and Times

Abstract: Background: Depending on the processing method, the raw materials constituents change in various ways. In particular, a heat treatment process, such as steaming, changes the color and aroma of a raw material to increase its palatability and number of physiologically active ingredients. Methods and Results: In the present study, the effects of the steaming temperature and time on the yield, color, proximal composition, and total polyphenol and ginsenoside content of a 4-year-old ginseng root were analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…According to Kwon et al (2006), in heated garlic, the total polyphenol content increased by approxi-mately seven times as the heating temperature increased, which is similar to a study that reported that the total polyphenol content increased as the heating temperature increased in various fruits and vegetables (Kim et al, 2008). The total polyphenol compound is more affected by the heating temperature than the heating time (Yu et al, 2019). This is because heat treatment converts the bound phenol component into a free form to facilitate dissolu-tion, or increase the content of phenolic compounds by decomposing the polymer phenol-ic compound into a low-molecular-weight phenolic compound (Koon et al, 2005).…”
Section: Total Polyphenol and Flavonoid Contentsupporting
confidence: 73%
“…According to Kwon et al (2006), in heated garlic, the total polyphenol content increased by approxi-mately seven times as the heating temperature increased, which is similar to a study that reported that the total polyphenol content increased as the heating temperature increased in various fruits and vegetables (Kim et al, 2008). The total polyphenol compound is more affected by the heating temperature than the heating time (Yu et al, 2019). This is because heat treatment converts the bound phenol component into a free form to facilitate dissolu-tion, or increase the content of phenolic compounds by decomposing the polymer phenol-ic compound into a low-molecular-weight phenolic compound (Koon et al, 2005).…”
Section: Total Polyphenol and Flavonoid Contentsupporting
confidence: 73%